Between Permanent Revolution and Permanent Liminality: Continuity and Rupture in the Bolivarian Government's Higher Education Reform. (January 2017) - Ivancheva, Mariya P.
After traditional academics mobilized university autonomy against government intervention and supported the coup d'état against Hugo Chávez, his government created a parallel system of public universities. María Egilda Castellano headed the effort to extend university access to poor Venezuelans. The events of her terms as vice minister of education (1999–2002) and rector of the Bolivarian University (2003–2004) and her subsequent career show the difficulty the Bolivarian government has had in creating sustainable institutions and challenge the applicability of the concept of permanent revolution to the Bolivarian process. Después de que los académicos tradicionales usaron la autonomía universitaria en contra de la intervención del gobierno y apoyaron el golpe de estado contra Hugo Chávez, su gobierno creó un sistema paralelo de universidades públicas. María Egilda Castellano dirigió el esfuerzo por extender el acceso a las universidades a los venezolanos pobres. Los resultados de su trabajo como vice ministra de educación (1999–2002) y rectora de la Universidad Bolivariana (2003–2004) y su subsiguiente carrera profesional demuestran la dificultad que el gobierno bolivariano ha tenido para crear instituciones sostenibles y pone en duda la aplicabilidad del concepto de revolución permanente al proceso bolivariano.